Benchmarking erasure coding schemes in openStack swift - Noor, Khandaker Ishrak; Noor, Yeasif Bin; Afrin, Shaima; Hossain, Mahanaj; Upoma, Rezuana Imtiaz (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.